INNOVATIVE APPROACHES TO IMPROVING THE QUALITY OF ENGLISH TEACHER TRAINING THROUGH IMPROVING NATIONAL AND GENERAL COMPETENCES (Universal International Scientific Journal, 2026)
This article discusses the scientific and methodological foundations and innovative approaches to improving national and intercultural competencies in the process of training future English teachers. It is argued that in the context of globalization, foreign language teachers need not only linguistic literacy, but also the ability to understand their own national culture, understand the cultural values ​​of other peoples, and have the skills of flexibility in the communication process. The study analyzes the effectiveness of using modern pedagogical technologies - media resources, digital educational platforms, interactive methods that develop intercultural communication. It also proposes a model for the integrated formation of national and intercultural competencies in English lessons.
Keywords: national competence; general cultural competence; future English teacher